Problem ustroju totalnego dla Polski w międzywojennej myśli politycznej i jako element propagandowy w krajowej historiografii powojennej - Grott, Bogumił (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The author investigated the growth of interest in the idea of total state which was observable in Polish political thought in the 1930s. This visible development was a consequence of the infiltration of foreign formulas which appeared in the interwar period in Fascist Italy, National Socialist Germany and, in a different version, in Soviet Russia. The crisis of a liberal democracy, readily apparent in Europe at the time, and internal conditions in the Second Polish Republic, characterized by the existence of numerous national minorities and sharp conflicts of social interests, also induced the search for new constitutional solutions. In light of this situation, there appears a question whether it looked like an idea of a totalitarian regime was to triumph in the Polish Republic? The detailed analysis of the relevant doctrinal enunciations and of the Polish cultural background Catholicism has led the author of the article to conclude that some interest in totalism, which peaked at the end of the 1940s, proved to be very superficial and ended in an option for a confessional state which was presaged by the “endecja” National Democracy project of the “Catholic State of Polish Nation.” Only a tiny nationalist group — so-called Falanga Phalanx — adopted a conception of “Catholic totalism” in which the Church and the institution of family were placed beyond the pale of political dominion. Grott states that only the Communist ideology and the ideology of the marginal neo-pagan, and at the same time collectivist, informal group Zadruga included the firm proposal to establish a total regime in Poland. The main reason for this unpopularity of totalism can be found in a fact that Catholicism which constituted one of the main components of the nationalist doctrine in Poland did not tolerate this system, perceiving it as a threat to the religion and the Church. The author also contends that the opinions of historians who accuse the National Democracy of supporting total solutions, lack foundation in scholarly sources and are either a result of the pressure of the Communist propaganda or a consequence of a deficiency of scientific method, the latter being an indispensable element of leading proper interdisciplinary research.
Keywords: totalitaryzm; Polska (1918-1939); myśl polityczna II RP; historiografia powojenna; katolicyzm